Rolnictwo ekologiczne w prawie wspólnotowym - Canfora, Irene (Wydawnictwo Naukowe UAM, 2008)
Regulation (EC) No 834/2007 concerning organic production and labelling introduces some important changes into European rules on organic farming. The paper deals with general objectives and principles that regulate the agricultural production and focuses on the environmental principle. There are two reasons for that. One, because it constitutes the natural prosecution of European rules concerning the promotion of environmental measures that find an important application in the case of agricultural producers applying for aid for organic farming. Moreover, environmental protection follows the consumers’ demand for organic products. Furthermore, it is discussed how new rules introduce a differentiation between national organic productions through flexibility principle. It gives the Member States the possibility to ask the Commission for specific derogations under Article 22 and by the provision allowing the Member States to use national labels for labelling and advertising of organic products. Under the above circumstances, innovative rules of Regulation 834/2007 provide new perspectives for the sphere of agricultural production regulation. This is because of the modifications to the original scheme of the European rules in this field which have become more characterised by national identification.

II regolamento nr 834/2007 relativo alia produzione biologica e alPetichettatura dei prodotti biologici introduce alcuni rilevanti cambiamenti nelle norme europee in materia di agricoltura biologica. Infatti, gli articoli introduttivi del regolamento trattano degli obiettivi generali e dei principi regolanti la produzione agrícola, focaüzzandosi sul principio ambiéntale e ció per due motivi. L’articolo si concentra sul principio ambiéntale in quanto esso costituisce un naturale evolversi delle norme europee riguardanti la promozione delle misure agro-ambientali che trovano un’applicazione importante nel caso dei produttori agricoli che richiedono l’aiuto per la produzione biologica. Inoltre, la tutela dell’ambiente caratterizza la richiesta di prodotti biologici da parte dei consumatori. Inoltre, si discute su come le nuove rególe possano influiré sulle diversitá tra le produzioni biologiche nazionali, essendo possibile invocare il principio di flessibilitá che offre agli Stati Membri la possibilitá di chiedere alia Commissione le specifiche deroghe di cui all ’art. 22, ed essendo poissibile l’utilizzo di etichette nazionali per la pubblicitá dei prodotti biologici. Considerando quanto appena detto, le nuove rególe del Regolamento 834/2007 danno una diversa prospettiva alia normativa in materia e ció attraverso la modifica delio schema origínale delle rególe europee in questo ámbito, modifica che consente una maggiore caratterizzazione nazionale.
Organic agricultural production in community law
L'agricoltura biologica nel diritto comunitario